PROSPEK AGROINDUSTRI SAGU DI SUMATERA BARAT KHUSUSNYA DI KEPULAUAN MEBNTAWAI - Gusmailina Gusmailina (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The potential of sago forest in Menlawai lslands has not yet been optimally exploited either as raw materia for industry and as food sources. This article is based on survey carried out in Mentawai islands, Wert Sumatera, on June 1991.40 % of Mentawm lsland are swamps and peals which the only possible exploitation of the area is through sago cultivation, that will produce sago as raw material for agroindustry.sago is abundantly avaiqble in the Mentawai Islands. Since man power and market, are no longer a problem, it is expected that sago industry would have a good prospect in the future.The lslands could pioneer the improvement of sago processing from traditional method to a relatively modern way. Hence, indirectly it would speed up the rate of economic development in the area.